Sistem Pendukung Keputusan Pencarian Rumah Tinggal Menggunakan Metode SMART - Isworo Nugroho; Hersatoto Listiyono; Dwi Agus Diartono; S Sunardi (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
The proses of searching for a residence has only observed the residence that will be chosen and does not have specific criteria in determining its choice, such as the distance from the residenceto work, shopping, city center, university, airport, price, free from flooding and the location of the residence. The search for a residential house needs several considerations that must be understood,such as consideration of price, land area, building area, mileage, and facilities in the residential house. This is one of the things that causes various problems faced in finding a house. The decision support system (DSS) for finding a residential house using the SMART method uses search criteria based on price, land area, building area, distance, and facilities. The results of the decision support system recommendations for finding a house using the SMARTs method will be sorted based on the largest SMARTs value to the smallest SMART value. This decision-making model using the SMARTs method can be further developed for more complex problems with a much larger number of criteria and alternatives.